2021
DOI: 10.1002/cncr.33677
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization plus lenvatinib versus transarterial chemoembolization plus sorafenib as first‐line treatment for hepatocellular carcinoma with portal vein tumor thrombus: A prospective randomized study

Abstract: BACKGROUND:The efficacy and safety of transarterial chemoembolization (TACE) plus lenvatinib in patients with hepatocellular carcinoma (HCC) and portal vein tumor thrombus (PVTT) have not been evaluated. METHODS: In this open-label, single-center, randomized trial (ClinicalTrials.gov identifier: NCT04127396), participants with previously untreated HCC and type I-IV PVTT were randomized 1:1 to receive TACE plus lenvatinib (arm L; orally once daily, 12 mg for body weight ≥60 kg or 8 mg for body weight <60 kg) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 32 publications
6
117
2
1
Order By: Relevance
“…Our results revealed that TACE-L achieved significantly better benefits with respect to PFS, OS, and ORR than TACE-S in HCC patients with PVTT. These results are similar to those of a previously published study ( 15 ), in which TACE-L was better than TACE-S in HCC with PVTT in terms of median TTP (4.7 vs. 3.1 months, p = 0.037) and numerically better median OS (15.6 vs. 10.8 months, p = 0.15) and ORR (50.0 vs. 25.0%, p = 0.07). In our study, we did not observe any significant differences in either OS or PFS in the entire cohort but only after PSM.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results revealed that TACE-L achieved significantly better benefits with respect to PFS, OS, and ORR than TACE-S in HCC patients with PVTT. These results are similar to those of a previously published study ( 15 ), in which TACE-L was better than TACE-S in HCC with PVTT in terms of median TTP (4.7 vs. 3.1 months, p = 0.037) and numerically better median OS (15.6 vs. 10.8 months, p = 0.15) and ORR (50.0 vs. 25.0%, p = 0.07). In our study, we did not observe any significant differences in either OS or PFS in the entire cohort but only after PSM.…”
Section: Discussionsupporting
confidence: 93%
“…Ding et al. have reported TACE-L vs. TACE-S in HCC patients ( 15 ). Our study offers a comparison of the efficacy between TACE-L and TACE-S in HCC patients with PVTT.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, systemic therapy is the key to improve the long-term prognosis, but unsatisfactory LC will impair the long-term survival advantage. Preclinical studies have identified the synergistic effect of TACE/HAIC and systemic therapy ( 20 , 21 ), which was also confirmed in practice of the combination of TACE and sorafenib ( 22 ), TACE and lenvatinib ( 23 ), HAIC and sorafenib ( 24 ), and HAIC plus lenvatinib and toripalimab ( 25 ), but it is not the end.…”
Section: Introductionmentioning
confidence: 79%
“…In this triple combination group, patients achieved a 67.9% ORR according to the mRECIST criteria, which significantly higher than that of dual combination, with an ORR of 33.2-46% ( 18 , 19 , 28 ) in PD-1/PD-L1 inhibitors combined with antiangiogenics, and 27.8-53.1% ( 29 , 30 ) in TACE combined with Lenvatinib. It has been found that the application of TACE alongside TKI and ICI resulted in more synergistic antitumor effects.…”
Section: Discussionmentioning
confidence: 80%